Governing urban diversity in Istanbul: Pragmatic and non-discriminatory solutions of governance initiatives in response to politicisation of diversity. (July 2019) - Yenigun, Ozge; Eraydin, Ayda
This paper examines the discourses and practices of central and local governments, as related to the issues of urban governance and diversity, and the emergence of new governance arrangements in different fields of Istanbul's diversity. The paper claims that current diversity discourses and policies in Turkey are being increasingly used as a rhetorical device to promote the economic development of the city, and to circumvent the different demands of people of diverse cultural, ethnic and religious backgrounds. In such processes of politicising diversity, governance initiatives undertake an important mission in coming up with pragmatic and non-discriminatory solutions to diversity-related issues. Through an examination of recent changes in the diversity policies of Istanbul and the emerging governance arrangements, this paper uncovers the conflicts and the mismatches that exist between the highly politicised discourses, policies and practices, and explores how different types of governance arrangements bring new arenas of expression to the diverse groups.